Two Cases of Pachydermodactyly Presenting as Polyarthritis. (17th January 2018) - Mititelu, Roxana; Finch, Sarah; Dancey, Paul; Landells, Ian
Abstract : Pachydermodactyly is characterized by asymptomatic, progressive swelling of the lateral aspects of the 2nd to 4th finger along the proximal interphalangeal (PIP) joint without involving the joint itself. We present 2 interesting cases of patients with periarticular swelling who were initially diagnosed and treated as juvenile idiopathic arthritis (JIA) with subsequent clinical and pathology confirmation of pachydermodactyly. These cases emphasize the importance of considering pachydermodactyly in young patients with development of periarticular swelling and no joint involvement.